HRM strategies for managing employee commitment: a case study of small construction professional services firms - Mohyin, Nur Affah; Dainty, Andy; Carillo, Pat (2012)
Construction professional services (CPS) rely heavily on the capabilities of their professional employees as their main resources in delivering their services. One of the main concerns in managing these workers is the development and maintenance of employee commitment towards achieving the organisational objectives. In achieving the desired commitment among employees, it is essential for organisations to carefully design and implement the right mix of human resource management (HRM) practices and strategies, and yet such strategies have received little attention within the construction management literature. Arguably, there is a possibility that small firm owner-managers have no coherent strategy for managing human resources aimed at developing employee commitment. Moreover, this research was conducted in a four-year period from the end of 2006 until 2010, during the time when the UK economy was hit by the global recession. Certainly, the external economic context provides more challenges for small CPS firms in managing the employment relationship. Accordingly, this research seeks to identify HRM practices that foster organisational commitment in small CPS firms. Two in-depth case studies were conducted, which included one small quantity surveying practice in the East Midlands, UK, and one small multi-disciplinary practice in the West Midlands, UK. The case studies involve in-depth interviews involving the employer and employees, participation observation and document analysis at the main office of both organisations. The findings highlight the importance of HRM in developing employee commitment. The five main HRM strategies to influence commitment are job design, performance and career management, training and development, reward management and employee involvement. All these HRM practices need to be effectively linked and managed appropriately to collectively foster the desired commitment, regardless of the economic climate. Finally, we conclude with limitations and implications of the findings that provide directions for future research.